1992
DOI: 10.1126/science.257.5069.524
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and Contrasting Effects of Habitat Fragmentation

Abstract: Different components of an ecosystem can respond in very different ways to habitat fragmentation. An archipelago of patches, representing different levels of fragmentation, was arrayed within a successional field and studied over a period of 6 years. Ecosystem processes (soil mineralization and plant succession) did not vary with the degree of subdivision, nor did most measures of plant and animal community diversity. However, fragmentation affected vertebrate population dynamics and distributional patterns as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(217 citation statements)
references
References 28 publications
10
201
0
4
Order By: Relevance
“…Most studies have focused on communities that were intact at the time of fragmentation, losing species following the fragmentation event. Relatively few studies have focused on the impacts of habitat fragmentation on community assembly (e.g., Simberloff and Wilson 1970;Robinson et al 1992). For instance, priority effects (Fukami 2015) and a combination of deterministic and stochastic processes may influence the trajectory of community assembly in fragmented systems (Norden et al 2015).…”
Section: Local Community-level Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused on communities that were intact at the time of fragmentation, losing species following the fragmentation event. Relatively few studies have focused on the impacts of habitat fragmentation on community assembly (e.g., Simberloff and Wilson 1970;Robinson et al 1992). For instance, priority effects (Fukami 2015) and a combination of deterministic and stochastic processes may influence the trajectory of community assembly in fragmented systems (Norden et al 2015).…”
Section: Local Community-level Dynamicsmentioning
confidence: 99%
“…Nonetheless, other measures of community structure, such as community composition, trophic organization, species persistence, and species residency, may better inform how fragmentation affects biotic communities, even when species richness per se is not altered by fragmentation (Robinson et al 1992;Haddad et al 2015). …”
Section: Key Findings Concerning Habitat Loss and Fragmentationmentioning
confidence: 99%
“…Even though area of the fragment and rarity of species should be good predictors of species occurrence in forest fragments (Andren, 1996), only a few studies have found this to be the case: temperate birds in Chile (Willson et al, 1994), rodents in USA (Robinson et al, 1992), birds in the rain forests of the Usambara mountains in Tanzania (Newmark, 1991), and primates in Brazil (Bierregaard et al, 1992). In contrast, many recent studies have shown that the persistence of a species in a fragmented habitat is related to isolation-mediated habitat variation, within and around the fragments, which are consistent with the ecology and behaviour of the species.…”
Section: Is Area Important?mentioning
confidence: 99%
“…These first-order impacts will likely engender a series of further consequences, including although not limited to: (i) fragmentation of species' ranges, with disruption of gene flow (25)(26)(27)(28); (ii) decline in effective population sizes, with depletion of gene reservoirs͞pools (12,29,30); and (iii) biotic interchanges introducing species and even biotas into new areas, with multiple founder effects and novel competitive and other ecological interactions (13,16,31). These impacts, in turn, might disrupt food chains͞webs, symbioses, or other biological associations (32,33).…”
Section: The Core Conceptmentioning
confidence: 99%